Hybridization between fiction and nonfiction in contemporary media culture: Nonfiction cinema in the spanish regulatory framework - Feria Sánchez, Juan José; Gómez Pérez, Francisco Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Contemporary media culture has reshaped the discursive boundaries between fiction and non-fiction, promoting experimentation and hybridization. This paradigm shift has impacted non-fiction cinema and its relationship with the film industry, particularly in its recognition as a cultural industry and, consequently, as an object of regulation and institutional support. This study examines, through a documentary content analysis of the main national and regional regulatory frameworks, the presence and conceptualization of non-fiction cinema in Spain, with a focus on aspects of message and discourse.